Factores explicativos del rendimiento escolar en Latinoamérica con datos PISA 2009 - Justo de Jorge-Moreno (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2016)
– This work has as main objective to determine the effect country, type of institution (its ownership, public or private) and their resources on educational outcomes for students of Latin-American education system from PISA 2009. The results obtained by applying a multilevel analysis reveal that differences in academic performance in favor of private schools are explained by the type of school providing empirical support for the hypothesis Coleman-Hoffer. The environment features student and school resources also have strong explanatory power. Regarding the former, native students in nuclear families with higher socioeconomic status and household resources get higher yields than other categories. This is especially significant in pointing out some aspects that the education system should take into account when ensuring equal educational opportunities. Regarding the latter, the size of the school, the classroom environment and the resources available in the centers have a strong influence on academic performance.
Keywords: H52; I21; I28; C38; 330; Latin America; socioeconomic status; peer effect; ownership; PISA 2009